Enlarged Thalamic Volumes and Increased Fractional Anisotropy in the Thalamic Radiations in Veterans with Suicide Behaviors - Lopez-Larson, Melissa; King, Jace B.; McGlade, Erin; Bueler, Elliott; Stoeckel, Amanda; Epstein, Daniel; Yurgelun-Todd, Deborah (Frontiers in Psychiatry, 2013)
Post-mortem studies have suggested a link between the thalamus, psychiatric disorders, and suicide. We evaluated the thalamus and anterior thalamic radiations (ATR) in a group of Veterans with and without a history of suicidal behavior (SB) to determine if thalamic abnormalities were associated with an increased risk of SB. Forty Veterans with mild traumatic brain injury (TBI) and no SB (TBI-SB), 19 Veterans with mild TBI and a history of SB (TB+SB) and 15 healthy controls (HC) underwent MRI scanning including a structural and diffusion tensor imaging scan. Suicidal behaviors were evaluated utilizing the Columbia Suicide Rating Scale and impulsivity was measured using the Barratt Impulsiveness Scale (BIS). Differences in thalamic volumes and ATR fractional anisotropy (FA) were examined between 1) TBI+SB versus HC and 2) TBI+SB versus combined HC and TBI-SB and 2) between TBI+SB and TBI-SB. Left and right thalamic volumes were significantly increased in those with TBI+SB compared to the HC, TBI-SB and the combined group. Veterans with TBI+SB had increased FA bilaterally compared to the HC, HC and TBI-SB group, and the TBI-SB only group. Significant positive associations were found for bilateral ATR and BIS in the TBI+SB group. Our findings of thalamic enlargement and increased FA in individuals with TBI+SB suggest that this region may be a biomarker for suicide risk. Our findings are consistent with previous evidence indicating that suicide may be associated with behavioral disinhibition and frontal-thalamic-limbic dysfunction and suggest a neurobiologic mechanism that may increase vulnerability to suicide.